1992
DOI: 10.1111/j.1469-7998.1992.tb07501.x
|View full text |Cite
|
Sign up to set email alerts
|

Intersexuality in the mysid Neomysis integer

Abstract: Intersexuality is described in Neomysis integer (Leach), apparently the first occurrence among the Mysidacea. Seven out of 13,700 specimens examined were masculinized females possessing elongated fourth pleopods, a male secondary sexual characteristic. Each masculinized female appeared to have reproduced as a normal female; there was no evidence of testicular tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Different hypotheses have been suggested to explain intersexuality in crustaceans, including parasitism (NIELSEN 1970, GINSBURGER-VOGEL 1991, genetic abnormalities (HOUGH et al 1992), environmental contamination (OLMSTEAD & LEBLANC 2007, MAZUROVÁ et al 2010, FORD 2012 and social organization (TÓTH & BAUER 2008). Since no bopyrid or rhizocephalan parasites were found associated with intersex Pisidia longicornis individuals, and no abnormalities were found on their carapace, pereopods, abdomen or pleopods, it is unlikely that macro-parasites are the cause of intersexuality in these crabs.…”
Section: Acknowledgements I Am Gratefully To Marcos Tavares (Mzusp) mentioning
confidence: 99%
“…Different hypotheses have been suggested to explain intersexuality in crustaceans, including parasitism (NIELSEN 1970, GINSBURGER-VOGEL 1991, genetic abnormalities (HOUGH et al 1992), environmental contamination (OLMSTEAD & LEBLANC 2007, MAZUROVÁ et al 2010, FORD 2012 and social organization (TÓTH & BAUER 2008). Since no bopyrid or rhizocephalan parasites were found associated with intersex Pisidia longicornis individuals, and no abnormalities were found on their carapace, pereopods, abdomen or pleopods, it is unlikely that macro-parasites are the cause of intersexuality in these crabs.…”
Section: Acknowledgements I Am Gratefully To Marcos Tavares (Mzusp) mentioning
confidence: 99%
“…Among invertebrates, molluscs show a similar phenomenon termed 'imposex', which is related to tributyltin (TBT) contamination (Gibbs et al 1991, Bettin et al 1996, Rank 2009). Crustacean intersexuality has been associated with natural events, such as viral infection (Juchault et al 1991), parasites (Ginsburger-Vogel 1991, hereditary factors including genetic abnormalities (Hough et al 1992), social (demographic) structure (Baeza & Bauer 2004), and abiotic factors (Bauer 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Intersexuality is a common phenomenon among species of other orders of peracaridan crustaceans. It has previously also been reported in representatives of the Isopoda, the Tanaidacea and the Amphipoda (HOUGH et aL, 1992).…”
Section: Neomysis Integermentioning
confidence: 80%
“…It is a hyperbenthic, euryhaline and eurythermic species, typically occurring in high numbers in estuarine, brackish water environments (TATIERSALL and TATTERSALL, 1951). HOUGH et al (1992) reported intersexual individuals of this species, Le. animals which display both male and female secondary sexual traits, from the Conwy estuary (north Wales).…”
Section: Neomysis Integermentioning
confidence: 97%
See 1 more Smart Citation